A New Copy of the Epic of Kadi and Ugru: Hikayet-i Kadi and Duzd - Muratoğlu, Murat (Turk Dil Kurumu, 2021)
Aside from their values as a literary genre, stories offer important data in terms of the social, cultural, political conditions and language characteristics of the period in which they were written. Turkish stories, the first examples of which we come across during the Old Uighur Turkish period, constitute an important corpus of Turkish language. One of them is the Epic of Kadi and Ugru, which is known to be written by Yusuf u Meddah in the XIVth century. The epic has many manuscripts in various libraries. The only copy of the work, which is thought to belong to Yusuf u Meddah, is registered in Suleymaniye Library with the catalog number Haci Mahmud Efendi 1930/5. The beginning part of this verse copy is missing. The work subject to this study is the new version of the Epic of Kadi and Ugru which is among the Turkish manuscripts made available to digital access by Leipzig Library under catalog number B.or.069-2 with title Hikayet-i Kadi ve Duzd. The copy was not shown in the copies identified in previous studies. There is no explanation in the text and catalog information about the author, date and place of the work. In the study, after giving information about the Epic of Kadi and Ugru, the content of the aforementioned new copy, its place among the other copies and its language features are emphasized. Accordingly, it can be said that the text was written in the Old Oghuz Turkish period. © 2021, Turk Dil Kurumu. All rights reserved.
Kadı ve Uğru Destanı’nın Yeni Bir Nüshası: Hikȃyet-i Kadı ve Düzd
Keywords: Old Oghuz Turkish; Story; The Epic of Kadi and Ugru; Yusuf U Meddah